Barriers to Diversity Management in Classroom: A Case of Rural Community Schools in Nepal - Sherpa, Dawa; Baraily, Khagendra (Tribhuvan University Journal, 2021)
This paper attempts to explore and analyse the barriers for diversity management in classroom of a rural community schools in Nepal. Nepal is a multi-ethnic, multi-lingual, and multi-cultural country. As the fabric of society, there is also diversity in the configuration of community schools in rural areas. It entails knowing that each student is unique and acknowledging their uniqueness in the classroom. These might be along the lines of color, ethnicity, gender, sexual orientation, socioeconomic position, age, physical ability, religious views, political convictions, or other ideologies. This paper is mainly based on primary and secondary data. Purposively, head teachers, teachers, and students were selected for interviews. Interviews, field visits, classroom observation, and focus group discussion with teachers and students were conducted, and the data were analyzed thematically based on interview codes. The data shows that they were ignorant of the concept of diversity and how to manage it in the classroom. It is mainly due to the deconstruction of teachers’ attitudes regarding income, professionalism, community structure, physical infrastructure, and socioeconomic discrepancies. This paper suggests managing diversity in the classroom through both policies to integrate curricula and effective management practices in the classrooms. Thus, teachers need pedagogical skills to address the issues of diversity, marginality and oppress groups of the society and barrier of diversity management in the classroom.